Modernism and popular music - Schleifer, Ronald (Cambridge, UK : Cambridge University Press, 2011)
'Traditionally, ideas about twentieth-century'modernism' - whether focused on literature, music or the visual arts - have made a distinction between'high' art and the'popular' arts of best-selling fiction, jazz and other forms of popular music, and commercial art of one form or another. In Modernism and Popular Music, Ronald Schleifer instead shows how the music of George and Ira Gershwin, Cole Porter, Thomas'Fats' Waller and Billie Holiday can be considered as artistic expressions equal to those of the traditional high art practices in music and literature. Combining detailed attention to the language and aesthetics of popular music with an examination of its early twentieth-century performance and dissemination through the new technologies of the radio and phonograph, Schleifer explores the'popularity' of popular music in order to reconsider received and seeming self-evident truths about the differences between high art and popular art and, indeed, about twentieth-century modernism altogether'--
'Introduction: popular music and the experience of modernism This is a book about the'cultural modernism' of the early twentieth century. Part I examines the place of popular music within conceptions of modernism, and Part II examines what I call'the rhythms and semiotics of language and sound' in the music of the Gershwin brothers, Cole Porter, Thomas'Fats' Waller, and Billie Holiday, with occasional references to modernist writers William Butler Yeats, T S. Eliot, Ralph Ellison, William Carlos Williams, Virginia Woolf, and others. The emphasis of Modernism and Popular Music is primarily linguistic or textual in that I am pursuing an account of how a'revolution in words,' as I note in the Conclusion, transformed or marked the ways in which sensibility, mind, belief, perspective, society, economics, and human experience more generally came to be understood in the early twentieth century. I argue, however, that this revolution, which is usually associated with poets, writers, artists, linguists, and philosophers - as well as twentieth-century composers of'art' music - is just as evident, if not more so, in the work of the great songwriters and jazz performers who came to prominence in the United States between the two World Wars'--
Includes bibliographical references (p. 216-225) and index.
Keywords: Gershwin, George, -- 1898-1937 -- Criticism and interpretation; Holiday, Billie, -- 1915-1959 -- Criticism and interpretation; Porter, Cole, -- 1891-1964 -- Criticism and interpretation; Waller, Fats, -- 1904-1943 -- Criticism and interpretation; Modernism (Music); Popular music -- United States -- History and criticism; Jazz -- History and criticism